2013
DOI: 10.1309/ajcp0n7ielyunjgz
|View full text |Cite
|
Sign up to set email alerts
|

IgM Multiple Myeloma

Abstract: The frequent B-cell-associated antigen expression by IgM MM distinguishes it from other MM types, causing significant pathologic overlap with lymphoplasmacytic lymphoma (LPL). However, IgM MM is usually distinguished from LPL by aberrant cyclin D1 expression or t(11;14). Therefore, assessing for these abnormalities is recommended when evaluating bone marrow involvement by IgM-associated lymphoplasmacytoid disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Due to the rare incidence of IgM myeloma, most of the current evidence relies on case reports and small case series [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19]. Herein, we present the clinicopathological characteristics, outcomes and prognostic factors identified in 159 IgM myeloma cases from 20 participating centers in Europe, United States and Latin America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rare incidence of IgM myeloma, most of the current evidence relies on case reports and small case series [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19]. Herein, we present the clinicopathological characteristics, outcomes and prognostic factors identified in 159 IgM myeloma cases from 20 participating centers in Europe, United States and Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…The cases of IgM myeloma described in the literature present with features typical of myeloma, including lytic bone lesions, hypercalcemia, renal failure, and decreased serum IgA and IgG levels [4]. However, IgM myeloma patients can also present with WM-like features such as lymphadenopathy and hyperviscosity, and IgM myeloma cells can express CD20 and have lymphoplasmacytoid morphology [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…5 Patients with IgM MM tend to have plasmacytic differentiation with high expression of CD138 and cytoplasmic immunoglobulin. 6 However, when patients present with IgM monoclonal gammopathy, osteolytic lesions, and lymphadenopathies or hepatosplenomegaly, untangling the MM-WM differential diagnosis can be challenging. 5…”
Section: Introductionmentioning
confidence: 99%
“…The presence of t(11;14) which leads to cyclin D1 dysregulation has been shown to be present in IgM MM according to recent studies, but absent in WM. 2 , 5 On the other hand, research has revealed the presence of a somatic mutation (MYD88 L265P) in patients with WM, identified by means of whole-genome sequencing and confirmed by Sanger sequencing. In contrast, MYD88 L265P mutation is absent in cases of myeloma, including IgM-secreting myeloma, making it useful as a distinguishing feature between WM and IgM MM.…”
Section: Introductionmentioning
confidence: 99%